THE FUNDAMENTALS OF HIGH-TECH SECTOR AND HIGH-TECH COMPANIES OPERATION - Svetlana V. Gavrilova (Статистика и экономика, 2016)
The article develops the concept of the«high-tech sector» and the «high-techcompany» as well as their differences and relation. Further the author accounts for the particularities of the high-tech company functioning compared to the common one. Finally the key factors and coreelements of high technology are identiﬁed.